Civil Defence and Protective Services in South Africa during World War Two, 1939–1945 (Historia, 2021)
During World War Two, South Africa inaugurated the Civilian Protective Services organisation as a civil defence effort to deal with, inter alia, the preventive and protective measures in defence of the civilian population against attack from the air and the sea, and against the dangers arising from sabotage and sudden emergency. Between 1940 and 1945, about 80 000 civilians volunteered for service in the air raid precautions and the civilian guard sections of the Civilian Protective Services, to contribute towards a national defence effort of the Union of South Africa. This article examines the origin of the Civilian Protective Services and its development during World War Two, within the context of South Africa's political and internal security challenges. It contends that the institution of the Civilian Protective Services was a vital element in South Africa's effort to enhance internal security, to assuage public anxieties and to sustain morale as well as to maintain public support for its war policy.
Keywords: World War Two; Civilian Protective Services; South Africa; propaganda; civil defence; aerial bombardment; H.G. Lawrence